Microsoft Windows server 2008 - Long, Mark.; Safari eBooks ([S.l.] : Virtual Training Co., 2008)
"Windows Server 2008 is Microsoft's newest server operating system. This new version is not just 'window' dressing, there are major architectural changes and major new enhancements that administrators will welcome. Microsoft has concentrated on enhancing security by reducing the attack surface and making enterprise administration and configuration more consistent. In this course, Mark Long will introduce you to what is new and different about this new server operating system, while reinforcing the foundation of the world's most popular server operating system. He will introduce you to the new management tools and scenarios, enhancements such as PowerShell, IPv6 and step you through the installation and basic setup of one of the most exciting new additions to the Windows Server family, ServerCore"--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher.
Title from resource description page (viewed Feb. 22, 2010).
Keywords: Directory services (Computer network technology); Microsoft Windows server; Electronic books